The situated deployment of the Italian presentative (e) hai. . ., '(and) you have. . .' within routinized multimodal Gestalts in route mapping with visually impaired climbers. (February 2023) - Simone, Monica; Galatolo, Renata
Drawing on video-recorded data from pre-climbing route mapping with visually impaired climbers and a sight guide, this study uses conversation analysis to investigate the situated deployment of the Italian presentative (e) hai '(and) you have' within locally routinized multimodal Gestalts. The study shows that the guide uses (e) hai to progress route mapping and engage the athlete in tactile actions that target specific features of the route. In this context, (e) hai is packaged with noun phrases, silent pauses, bodily movements, and touch. The arrangement of such syntactic and embodied components is shown to follow a recurrent trajectory in which, between (e) hai and its grammatical completion, syntactic suspension creates a dedicated slot for guide and athlete to physically attain the target object. Routine embeddedness of (e) hai within such arrangement is shown to provide specific affordances to the athletes to anticipate subsequent action and engage in its embodied implementation.